Energy Crisis vs. Energy Self-Sufficiency: Optimal Policy with Firms Investment Behavior - Gaeta, Emanuela Giusi (Current Aspects in Business, Economics and Finance Vol. 4, 2022)
After the Ukraine war, the choice of the optimal policy for the country's energy self-sufficiency from primary sources can be seen as the geopolitical balance in the international scenario. The paper shows that energy self-sufficiency is possible for countries, if the oil price is high enough to induce firms to adopt alternative energy sources. The research demonstrates this result, by introducing an oil tax (to increase oil price), as a policy tool for achieving energy self-sufficiency, in presence of alternative energy (oil) saving technologies and scarce resources in competitive markets. The policy instrument reflects what the German government is going to apply to gas sources, in order to reduce the gas demand from Russia. The paper also makes a static comparison of different scenarios, where the regulator moves first (or not), with respect to the firms. Multiple equilibria are possible, but there is the only one that is socially optimal and the study shows that taxation affects the adoption of different energy saving technologies, hence the aggregate amount of oil, thanks to the adoption of alternative sources, that is the energy self-sufficiency’s requirement.